Mitred architraves and simple rebated reveals of a panel door in a sandstone cottage, Liverpool Street, Hobart, Tasmania, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting wooden panel doors, hall clock.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 2 24 5.
Published in: Australian colonial architecture / Philip Cox, Clive Lucas ; selected photographs by Wesley Stacey. Melbourne : Lansdowne Editions, 1978., p. 83.
Also available online
Keywords: Doorways -- Tasmania -- Hobart -- Photographs; Wooden doors -- Tasmania -- Hobart -- Photographs; Cottages -- Tasmania -- Hobart -- Photographs; Architecture, Georgian -- Tasmania -- Hobart -- Photographs; Hobart (Tas.) -- Buildings, structures, etc -- Photographs